Evaluation of Rice (Oryza sativa L.) based Cropping Systems in Major Soil Series of upper Brahmaputra Valley Asom (Global Journal of Science Frontier Research, 2014)
On farm field experiments were conducted during 2005 to 2008 to evaluate production and land use efficiency of rice (Oryza sativa L.) based cropping systems in four major soil series of upper Brahmaputra valley of Asom. The rice cultivar Basundhara and Satyaranjan were followed by three winter crops viz., potato (Solanum tuberosum), peas (Pisum sativum) and mustard (Brassica nigra) on four major soil series viz., Lahangaon (Aeric Fluvaquents), Bhogdai (Fluvaquventic Endoaquepts), Matikhola (Typic Endoaquepts) and Teok (Typic Fluvaquents) of Jorhat district in split-split plot design under farmers practice (FP) and recommended package of practices (RPP). The pooled data on rice equivalent yield (REY) of rice-potato Lahangaon series (156.6 q ha-1) under RPP was found economically significant followed by Bhogdai (138.4 q ha-1) and Matikhola (111.07 q ha-1) but rice -pea (100.9 q ha-1) in Teok series. The high production efficiency is recorded for rice-pea system with mean of 54.95 kg ha-1day-1 and highest of 66.7 kg ha-1day-1 in Lahangaon series and an increase of land use efficiency from 35 to 70 percent. The agronomic performance of rice based systems under RPP was well over FP at all the soil series, but best results were recorded at Lahangaon series.
Keywords: rice; winter crops; soil series; brahmaputra valley